A history of the world semi-conductor industry - Morris, P. R. (Peter Robin) (London, United Kingdom Institution of Engineering and Technology, 1990)
The following topics are dealt with: thermionic valve; transistor development; semiconductor device fabrication; and the semiconductor industry.
Electronic reproduction.
Keywords: Semiconductor industry -- History; Semiconductors -- History; Electronic books